Mixed‐methods approach to exploring patients' perspectives on the acceptability of a urinary biomarker test in replacing cystoscopy for bladder cancer surveillance. (4th March 2019) - Tan, Wei Shen; Teo, Chin Hai; Chan, Delcos; Heinrich, Malgorzata; Feber, Andrew; Sarpong, Rachael; Allan, Jennifer; Williams, Norman; Brew‐Graves, Chris; Ng, Chirk Jenn; Kelly, John D.; ,
Abstract : Objectives: To determine the minimal accepted sensitivity (MAS) of a urine biomarker that patients are willing to accept to replace cystoscopy and to assess qualitatively their views and reasons. Patients and Methods: Patients were part of a prospective multicentre observational study recruiting people with bladder cancer for a urine biomarker study (DETECT II; ClinicalTrials.gov: NCT02781428). A mixed‐methods approach comprising (1) a questionnaire to assess patients' experience with cystoscopy and patients' preference for cystoscopy vs urinary biomarker, and (2) semi‐structured interviews to understand patient views, choice and reasons for their preference. Results: A urine biomarker with an MAS of 90% would be accepted by 75.8% of patients. This was despite a high self‐reported prevalence of haematuria (51.0%), dysuria/lower urinary tract symptoms (69.1%) and urinary tract infection requiring antibiotics (25.8%). There was no association between MAS with patient demographics, adverse events experienced, cancer characteristics or distance of patients' home to hospital. The qualitative analysis suggested that patients acknowledge that cystoscopy is invasive, embarrassing and associated with adverse events but are willing to tolerate the procedure because of its high sensitivity. Patients have confidence in cystoscopy and appreciate the visual diagnosis of cancer. Both low‐ and high‐risk patients would consider a biomarker with a reported sensitivity similar to that of cystoscopy. Conclusion: Patients value the high sensitivity of cystoscopy despite the reported discomfort and adverse events experienced after it. The sensitivity of a urinary biomarker must be close to cystoscopy to gain patients' acceptance.